Mass horrors and unconditional obedience (2014)
Unconditional obedience fundamentallyquestions our humancondition, our relation to guilt, andthe capacity to be responsible forour acts. On the basis of testimoniesof mass murders, this text exploresthe type of denial operating in therefusal to know what led the assassinsto obey unreasonable orders.